A changing gastric environment leads to adaptation of lipopolysaccharide variants in Helicobacter pylori populations during colonization. - Anna Skoglund; Helene Kling Bäckhed; Christina Nilsson; Britta Björkholm; Staffan Normark; Lars Engstrand (PLoS ONE, 2009)
The human gastric pathogen Helicobacter pylori colonizes the stomachs of half of the human population, and causes development of peptic ulcer disease and gastric adenocarcinoma. H. pylori-associated chronic atrophic gastritis (ChAG) with loss of the acid-producing parietal cells, is correlated with an increased risk for development of gastric adenocarcinoma. The majority of H. pylori isolates produce lipopolysaccharides (LPS) decorated with human-related Lewis epitopes, which have been shown to phase-vary in response to different environmental conditions. We have characterized the adaptations of H. pylori LPS and Lewis antigen expression to varying gastric conditions; in H. pylori isolates from mice with low or high gastric pH, respectively; in 482 clinical isolates from healthy individuals and from individuals with ChAG obtained at two time points with a four-year interval between endoscopies; and finally in isolates grown at different pH in vitro. Here we show that the gastric environment can contribute to a switch in Lewis phenotype in the two experimental mouse models. The clinical isolates from different human individuals showed that intra-individual isolates varied in Lewis antigen expression although the LPS diversity was relatively stable within each individual over time. Moreover, the isolates demonstrated considerable diversity in the levels of glycosylation and in the sizes of fucosylated O-antigen chains both within and between individuals. Thus our data suggest that different LPS variants exist in the colonizing H. pylori population, which can adapt to changes in the gastric environment and provide a means to regulate the inflammatory response of the host during disease progression.